Effect Of Educational Media Picture Card On Knowledge Of Fire Disaster Response In School-Age Children - Fera Utami; Imardiani; Siti Romadoni (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Background: Every year cases of fire disasters have increased. Fire disasters can occur anywhere resulting in victims and loss of property. Fire disasters can occur in adults, the elderly and also children. Children are included in communities that are often at risk of the impact of fire disasters, because their skills and knowledge are still considered to be lacking which is the reason children become victims. Prevention efforts that can be done by providing education as early as possible to children about fire emergency response, one of the media that can be used for school-age children is media picture cards in the form of pictures and explanations that are easy for school-age children to understand and remember. Research Objectives: To determine the effect of educational media picture cards on knowledge of fire emergency response in school-age children. Research Method: Type of quantitative research with a Pre-Experimental approach using the One Group Pretest-Posttest Design. The sample involved 74 respondents by selecting the sample with the Total Sampling technique. The research instrument uses picture cards and knowledge questionnaire sheets about fire emergency response. Data analysis using the Wilcoxon statistical test. Results: The median value before being given education was 14.00 and after being given education it was 19.00 so that there was a significant difference between before and after education on picture card media on fire disaster emergency response knowledge obtained value (P Value = 0.001). Conclusion: There is an educational effect of picture card media on knowledge of fire emergency response in school-age children.